Pochłanianie CO2 przez polskie ekosystemy leśne - Gaj, Kazimierz (Leśne Prace Badawcze, 2012)
This paper presents a method for estimating the balance of carbon dioxide (CO 2 ) emission and absorption by Polish forest ecosystems. Based on the existing literature, a method for estimating the net absorption of CO 2 and a synthetic index to assess this amount per hectare per year was developed. The calculation was derived using two alternative methodologies. The first is based on estimating the amount of CO 2 sequestered over a trees’ life, and the second based on estimating the age-dependent biomass growth of trees. Obtained results indicate that total CO2 sequestration by Polish forest ecosystems is the equivalent of approximately 25% of Polish anthropogenic carbon emissions and suggest that previous calculations may have been underestimated.